Penerapan Strategi Team Games Tournament Untuk Meningkatkan Partisipasi Belajar IPA Pada Siswa Kelas V SD Negeri Karanganom 2 Sukodono Sragen Tahun Ajaran 2015/2016 - Wicaksana, Kukuh, Dra. Risminawati, M.Pd, Drs. Suwarno, SH. M.Pd (2016)
Education is an important part in improving the quality and the quality of a person, but the reality on the ground looks more teacher dominated learning so that students become passive, this has resulted in low participation of IPA learn that adversely affects the student learning outcomes. The purpose of this study to increase participation to learn science through the use of strategies Team Games Tournament in Class V SD Negeri Karanganom 2, Sukodono, Sragen, the academic year 2015/2016. Model of research is a classroom action research subjects teachers and students of class V and the object of the research is the strategy TGT and Participation learn science. The results showed an increase study participation in science subjects. In the pre-action average percentage of student participation by 35%, increased in the first cycle of 52% and increased in the second cycle of 84%. The conclusion reached by the use of Team Games Tournament strategy has proven effective and have a positive impact for students of classes V Elementary School Karanganom 2 Sukodono where at each meeting proved to be an increase in participation and learning outcomes in science subjects. Keywords: learning participation, Team Games Tournament